Detection of methicillin-resistant Staphylococcus aureus using mecA/nuc genes and antibiotic susceptibility profile of Malaysian clinical isolates. - Ali, Abd Manaf; Suhaili, Zarizal; -, Saiful; -, A.J.a (2006)
The aim of this study is to compare methicillin-resistant Staphylococcus aureus (MRSA) detection methods and to gene rate antibiogram profile of S. aureus clinical isolates from two teaching hospitals in Malaysia including three reference isolates from American Type Culture Collection (ATCC). The mecA/nuc gene PCR amplification, spot inoculation test and oxacillin disc diffusion test were applied to compare its MRSA detection abilities. No disagreement between the three methods was observed. From 29 bacterial isolates (including the ATCC strains) tested, 19 isolates were confirmed as S. aureus with 14 isolates exhibiting multidrug-resistance. All isolates are still susceptible to vancomycin as indicated by the E-test result. Current biochemical tests are comparable with the molecular detection method for MRSA used in this study while multidrug-resistance traits are present in both MRSA and MSSA clinical isolates. Presently, mupirocin seems to be the best alternative for vancomycin against multidrug-resistant S. aureus infections in Malaysia. Susceptibility profile of 19 S. aureus isolates acquired from two teaching hospitals and ATCC towards 16 selected antibiotics was analyzed and an antibiogram was generated. Findings also indicated resistance against many of the available antibiotics and thus an urgent need to search for alternative antibiotics.